Konfeksiyon işletmelerinde maliyet organizasyonu - Şahin, Ayşegül (My University, 2002)
Bu yüksek lisans tezimin konusu Konfeksiyon İşletmelerinde Maliyet Organizasyonudur. Konfeksiyon sektörü sağladığı istihdam imkanları, üretim sürecinde oluşturduğu katma değeri ve ihracat gelirleri içerisindeki yüksek payı nedeniyle ülke ekonomimizde kalkınma sürecinde en önemli sektörlerden biri olmuştur. Konfeksiyon sektörünün üretim yapısı emek yoğun tarzdadır. Dünyada tekstil üretimindeki gelişmeler hızla artarken, konfeksiyon üretimi işgücü maliyetlerinin ucuz olduğu gelişmekte olan ülkelere doğru kaymaktadır. İşletmelerde maliyet oluşumu, işletmenin kendi ürettiği mamulun cinsine, işletmenin büyüklüğüne ve organizasyon yapısına göre belirlenir. Öte yandan işletmenin maliyet sisteminin belirlenmesi ve üretim giderlerinin izlenmesi için etkin bir Maliyet Muhasebesi Organizasyonuna ihtiyacı vardır. Çalışmanın birinci bölümünde, Konfeksiyon İşletmelerinin tanımı ve sınırlaması yapılmış, ikinci bölümde Dünyada ve Türkiye'de konfeksiyon sanayinin yapısı üzerinde durulmuştur. Üçüncü bölümde, Konfeksiyon İşletmelerinde Maliyet Muhasebesi Organizasyonu başlığı altında, muhasebe ve maliyet muhasebesi organizasyonun nasıl oluşturulacağı, üretim giderlerinin izlenmesi ve sipariş maliyetinin saptanması üzerinde durulmuştur.Dördüncü bölümde, konfeksiyon işletmelerinde maliyet organizasyonu ile ilgili uygulama örneğine yer verilmiştir. Beşinci bölümde inceleme sonucu varılan sonuç, altıncı bölümde ise kullanılan kaynaklar yer almaktadır. Türk konfeksiyon sektörü ucuz ve nitelikli işgücü, hammadde kaynaklarına sahip olma, Avrupa pazarına coğrafi yakınlık gibi avantajlarıyla uluslararası pazarda önemli bir konum elde etmiştir. Name and Surname : Ayşegül ŞAHİN Department: Business Management Program : Accounting - Finance Dissertation Supervisor: Assoc. Prof. Gürbüz GÖKÇEN Dissertation Type and Date: Master Degree - October 2002 Ready-Made Clothing Companies, Accounting Organisation.

The subject of this dissertation for master degree is the Cost Organisation in Ready-Made Clothing Industry Companies. Ready-Made Industry has always been one of the most significant sectors in the development process of our country's economy due to the employment opportunities that it offers, the value added in the production process and its high ratio in the export incomes. The production structure of the ready-made industry is composed of a labour-based pattern. While the developments in the textile production have been gradually increased all over the world, the line of ready-made clothing production has been oriented towards the underdeveloped countries where the costs of labour and workmanship are cheap and cost-effective. The accrual of costs in the companies is determined in accordance with the type of the products that the company produces, the size of the company and its organisational structure. On the other hand, there is a requirement for an efficient Cost Accounting Organisation for the determination of cost system of the company and monitoring the production expenses. In the first section of this study hereby, the definitions of Ready-Made Clothing Companies have been provided and the relevant limitations have been given. In the second section, the structure of the ready-made industry currently effective in the world and in Turkey has been dealt with. Titled as Cost Accounting Organisation in the Ready-Made Clothing Companies, the third section deals with the methods for the application of accounting and cost accounting organisation, the follow-up of the production expenses and the determination of the cost of orders. In the fourth section, some practical application examples related with the cost organisation in ready-made clothing companies have been provided. In the fifth section, the conclusion drawn from the study has been explained and in the sixth section, the relevant bibliography used as reference in the study has been listed. Turkish ready-made clothing sector has acquired a place of critical importance in the international markets due to its advantages originating from its cheap and qualified labour and raw material sources, geographical proximity to European markets, etc.
Keywords: Maliyet ve Yönetim